Climate change education on promoting environmental literacy of high school teachers in Iran - Zamani, Anahita; Karimzadegan, Hasan; Almolouk Lahijanian, Akram (Scientific Journal of Environmental Sciences, 2017)
One of the most important things to solve environmental problems, increase knowledge and awareness is that this matter needs education. The aim of this study was to increase the level of environmental literacy teachers and school districts Ray first man to approach the effects of climate change. The current research method is descriptive and functional and experimental methodology and systematic random sampling from the first secondary school teachers of social studies lesson ninth base is used. To collect the required data using a questionnaire and the results of Cronbach’s alpha (r=0.80) has shown that the questionnaire had high reliability. The results show a significant difference between promoting environmental literacy teachers before and after the training effects of climate change there. But significant differences between teachers in environmental protection, climate change effects, there is no before and after training. No significant difference before and after the intervention to reduce the consequences of climate change impact of climate change on the environment does not exist. No significant difference before and after the training effects of climate change to provide appropriate recommendations to mitigate the effects of climate change does not exist on reducing the environmental consequences of climate change showed that there is no significant difference between mitigation and education and training to allay the consequences of climate change does not cause.